Republic of Tajikistan : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by Executive Director for the Republic of Tajikistan. (IMF Staff Country Reports; Country Report ;, 2022)
With a strong recovery in train, the authorities are gradually withdrawing the policy stimulus released during the pandemic. Although debt is sustainable, there is a high risk of debt distress. At the same time, financing the Roghun dam project while implementing tax reform remains a key challenge. The financial sector has stabilized, but intermediation remains low. Risks to the outlook are tilted to the downside due to uncertainty on the pandemic and regional spillovers.